Demography and well-being - Clark, Andrew E. (Vienna yearbook of population research, 2021)
Demography studies the characteristics of populations. One such characteristic is well-being: this was the subject of the 2019Wittgenstein Conference. Here, I discuss how objective well-being domains can be summarised to produce an overall well-being score, and how taking self-reported (subjective) well-being into account may help in this e ort. But given that there is more than one type of subjective well-being score, we would want to know which one is “best”. We would also need to decide whose well-being counts, or counts more than that of others. Finally, I briefly mention the potential role of adaptation and social comparisons in the calculation of societal well-being.